Player`s success prediction in rugby union: From youth performance to senior level placing - Colosio, A.; Fontana, F. Y.; da Lozzo, G.; Pogliaghi, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Union Rugby National federations and clubs regularly engage in youth draft camps, where anthropometric and functional characteristics are evaluated towards early talent identification and selection of the potentially elite athletes. Yet the relative predictive power of single characteristics in future career development remains to be determined. PURPOSE: this study aims at determining if and to what extent specific anthropometric and functional characteristics can accurately predict subsequent career progression. METHODS: Anthropometric and functional characteristics of 531 male players in the U16 age category, as recorded during 2006-09 Italian National Draft Camps, were retrospectively analysed in relation to senior level placing at age 21-24. Players were classified as International (I, National team and international clubs) or National (N, 1st, 2nd and other divisions, dropout). Multivariate analysis of variance (One-way MANOVA) tested the difference between I and N along a combination of anthropometric (weight, height, body fat, fat-free mass) and functional variables (SJ, CMJ, t15m, t30m, VO2max). A Discriminant function (DF) was determined to predict group assignment based on a linear combination of variables and corresponding coefficients. Correct level assignment was expressed as % hit rate. RESULTS: The youth players enrolled in draft camps represent a very selected sample that does not reflect the anthropometric characteristics of the reference population (> 95th percentile for weight and height). 39 players (7%) were classified as I, while 492 (93%) were classified as N. The results of MANOVA analysis indicate that a combination of anthropometric and functional characteristics reflects future level assignment (I vs. N) (V = 0.27, F(28, 1356) = 3.45, p < 0.05). Furthermore, players` success can be accurately predicted (hit rate = 81% and 77% for I and N respectively) by a DF (. = 0.88, 2 = 45.1, p < 0.05) that combines anthropometric and functional variables as measured at ~15 years of age. Among these, % body fat and speed appear to be the most influent predictors of group stratification within the discriminant function. CONCLUSIONS: Within a group of 15 year-olds with exceptional physical characteristics, future player`s success can be predicted using a linear combination of anthropometric and functional variables, among which a lower % body fat and higher speed over a 15m sprint provide the most important predictors of the highest career success. The early identification of the athlete`s potential allows to "customise" the development programme based on the individual`s needs and deficits and to maximise the overall efficiency of the formation process.